PERSEPSI DAN PENGARUH KEMUDAHAN FINTECH DALAM PELAYANAN KEPUASAN PELANGGAN YANG MENDORONG AKSELERASI KINERJA UMKM MAGELANG - Sriyono, Sriyono; Fadilah, Nur; Diansyah, Reni Nur; Teaningrum, Ratna Yulis (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study is to determine the effect of Fintech convenience in service on customer satisfaction. Customer satisfaction can be interpreted as a need that the customer wants to feel, and based on this experience, the customer has to experience it, and based on this experience, the customer considers whether it is worth visiting again. Satisfaction can also be interpreted as exploring the nature of the goods or services themselves, which provides a measure of customer satisfaction related to meeting consumer needs. This study uses descriptive qualitative analysis, collecting information from all the information about the themes and subjects discussed. The use of data collection techniques is a literature review approach using various excavation journals, articles, and secondary data. Quarrying data is collected and used as the main source of information. This research examines how fintech is applied to the development of SMEs. Based on research on the impact of fintech on SMEs, The Impact of Fintech on SMEs Based on research results, it can be said that 27.8% of MSME actors in Magelang City have implemented Fintech, but not all MSME actors in Magelang City have implemented Fintech.